Green Synthesis and Characterization of ZnO Nanoparticles from Cynoglossum microglochin Extract with Broad Spectrum Antioxidant, Antileishmanial, Antibacterial and Anticancer Activities - Beenish Kalsoom; Ishtiaq Hassan; Abdul Basit; Ikram Ullah; Muhammad Tariq; Manan Khan; Inam Ullah (Journal of Pharmaceutical Innovation, 2027)

Multifunctional bioactive films based on carboxymethyl cellulose/sodium alginate incorporated with DES-lignin-stabilized ginger oil nanoemulsion and gallic acid for enhanced shelf-life of cherry tomatoes - Asad Mukhtar; Muhammad Abdur Rehman Shah; Haoxin Li; Xiaojie Yu; Albert Abugri; Allah Rakha; Rana Abdul Basit; Areej Munir; Li Chen; Hua Yang; Cunshan Zhou (Food Hydrocolloids, 2026)

In-situ plasma treatment and low-temperature lithicone protective layer for interfacial stability of ultrathin Li metal anodes - Ha Yeon Kwon; Kyu Moon Kwon; Min Jung Choi; Syed Jazib Abbas Zaidi; Muhammad Abdul Basit; Ji-Hoon Ahn; Woo-Hee Kim; Seung-Jeong Oh; Hyo Rang Kang; Tae Joo Park (Chemical Engineering Journal, 2026)

Enhancing skin moisture and anti-aging by DL-α-tocopherol loading sodium alginate-based hydrogel microneedles - Khan Manqoosh Awan; Haojie Yu; Li Wang; Muhammad Haroon; Abdul Basit; Jian Hu; Jingyi Feng; Muhammad Owais Malik; Dileep Ahmad; Saqlain Raza; Hammal Majeed (Drug Delivery and Translational Research, 2026)

Mechanistic insights into bubble growth dynamics and water electrolysis performance regulated by electrode wettability - Jiaxuan Hu; Muhammad Abdul Basit; Guohao Du; Changqing Guo; Liqiao Jiang; Changfeng Yan (Fuel, 2026)

Identifying phytoremediation potential of ten tobacco varieties: Cadmium-induced hormesis, bioaccumulation and translocation - Shaista Jabeen; Muhammad Abdul Basit; Ahmed Mukhtar; Muhammad Tauseef Jaffar; Muhammad Ahmed; Lixin Zhang (Journal of Environmental Management, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Nigella sativa L. (Black cumin) seeds impart protective effects against Staphylococcus aureus induced septic arthritis through the modulation of immune and inflammatory responses - Muhammad Aamir Shaheen; Adeel Sattar; Huma Rao; Amjad Riaz; Abdul Basit (Food Bioscience, 2026)

Year-round strawberry production: advancements in forcing techniques to extend the growing season - Izhar Ullah; Leyla Demirsoy; Abdul Basit; Khurram Shahzad; Muhammad Danish Toor; Attiq ur Rehman (Planta, 2026)

Integrating organic and inorganic amendments to enhance wheat growth, physiology and antioxidant activity while reducing cadmium accumulation - Ahmad Ali; Zaffar Malik; Muhammad Abdul Basit; Abubakar Dar; Usman Zulfiqar; Dilnoza Sotiboldiyeva; Muydinjon Muminov; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Morphology and phylogeny of gasteroids and two novel hosts for Pisolithus albus (Sclerodermataceae) from Pakistan - Fahim Hussain Shah; Munazza Kiran; Muhammad Binyamin Khan; Abdul Basit; Abdallah M. Elgorban; Mushtaq Ahmad; Tauseef Ullah; Abdul Samad Mumtaz; Sana (New Zealand Journal of Botany, 2025)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Assessment of microbial remediation potential of indigenous bacterial and fungal communities for toxic heavy metal sequestration - Afnan Khalid; Haris Maqbool; Izhar Khan; Basit Khan; Iffat Naz; Shanza Abdul Qayyum; Javed Ali; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2025)

Evaluating the cooling potential of urban green spaces in Faisalabad integrating invest urban cooling model with multisource remote sensing data - Hafiz Abdul Basit Zaid; Usman Mahmood Mughal; Muhammad Amin; Meer Muhammad Sajjad; Muhammad Farhan; Amir Sattar; Shujaat Ali; Mujtaba Ali; Qurat ul Ain (Theoretical and Applied Climatology, 2025)

MXenes: From functional innovations to solving global environmental and energy crises – A comprehensive overview and perspective - Abdul Basit; Tahir Rasheed; Haiqa Maqsood; Sana Qureshi; Shaista Zubaid; Muhammad Tuoqeer Anwar; Ali Arishi; Tauqir A. Sherazi (Journal of Environmental Chemical Engineering, 2025)

A critical review on pear Fruit’s polyphenols and its chlorogenic acid: Composition, bioavailability, and pharmacological potential - Abdul Basit; Raheem Shahzad; Abdul Mueed; Asim Muhammad; Wang Rong; Liu Ya; Gong Xin; Khanizadeh Shahrokh; Muhammad Arshad; Tao Shutian (Food Bioscience, 2025)

Revealing Effects of Calcium-Based Formulations Focusing on Membrane Instability, Fruit Quality, Phytochemical Properties, and Disease Incidence in Peach (Prunus Persica) During Storage - Syed Tanveer Shah; Muhammad Sajid; Abdul Basit; Bibi Haleema; Ayesha Khan; Heba I. Mohamed (Applied Fruit Science, 2025)

A survey of quantifying food waste from hotel restaurants and caterers in Multan, Southern Punjab, Pakistan - Abdul Basit; Nida Urooj; Muhammad Humza; Muhammad Salman Hameed (Food and Humanity, 2025)

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

Navigating Climate Change: Exploring the Dynamics Between Plant–Soil Microbiomes and Their Impact on Plant Growth and Productivity - Murad Muhammad; Abdul Wahab; Abdul Waheed; Khalid Rehman Hakeem; Heba Ibrahim Mohamed; Abdul Basit; Muhammad Danish Toor; Yong‐Hong Liu; Li Li; Wen‐Jun Li (Global Change Biology, 2025)
Understanding the intricate interplay between plant and soil microbiomes and their effects on plant growth and productivity is vital in a rapidly changing climate. This review explores the interconnected impacts of climate change on plant–soil microbiomes and their profound effects on agricultural productivity. The ongoing rise in global temperatures, shifting precipitation patterns and extreme weather events significantly affect the composition and function of microbial communities in the rhizosphere. Changes in microbial diversity and activity due to rising temperatures impact nutrient cycling, microbial enzyme synthesis, soil health and pest and disease management. These changes also influence the dynamics of soil microbe communities and their capability to promote plant health. As the climate changes, plants' adaptive capacity and microbial partners become increasingly crucial for sustaining agriculture. Mitigating the adverse effects of climate change on plant growth and agricultural productivity requires a comprehensive understanding of the interconnected mechanisms driving these processes. It highlights various strategies for mitigating and adapting to environmental challenges, including soil management, stress‐tolerant crops, cover cropping, sustainable land and water management, crop rotation, organic amendments and the development of climate‐resilient crop varieties. It emphasises the need for further exploration of plant–soil microbiomes within the broader context of climate change. Promising mitigation strategies, including precision agriculture and targeted microbiome modifications, offer valuable pathways for future research and practical implementation of global food security and climate change.

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Exploring Marine Cloud Brightening with a Reduced Complexity Model - Muhammad Mueed Khan; Christopher Runyan; Shahzad Bashir; Abdul Basit Amjad (Journal of Meteorological Research, 2024)
Throughout the industrial period, anthropogenic aerosols have likely offset approximately one-third of the warming caused by greenhouse gases. Marine cloud brightening aims to capitalize on one aspect of this phenomenon to potentially mitigate global warming by enhancing cloud reflectivity through adjustments in cloud droplet concentration. This study employs a simplified yet comprehensive modeling framework, integrating an open-source parcel model for aerosol activation, a radiation transport model based on commercial computational fluid dynamics code, and assimilated meteorological data. The reduced complexity model addresses the challenges of rapid radiation transfer calculations while managing uncertainties in aerosol–cloud-radiation (ACR) parameterizations. Despite using an uncoupled ACR mechanism and omitting feedback between clouds and aerosols, our results closely align with observations, validating the robustness of our assumptions and methodology. This demonstrates that even simplified models, supported by parcel modeling and observational constraints, can achieve accurate radiation transfer calculations comparable to advanced climate models. We analyze how variations in droplets size and concentration affect cloud albedo for geoengineering applications. Optimal droplet sizes, typically within the 20–35-µm range, significantly increase cloud albedo by approximately 28%–57% across our test cases. We find that droplets transmit about 29% more solar radiation than droplets. Effective albedo changes require injection concentrations exceeding background levels by around 30%, diminishing as concentrations approach ambient levels. Considerations must also be given to the spray pattern of droplet injections, as effective deployment can influence cloud thickness and subsequently impact cloud albedo. This research provides insights into the feasibility and effectiveness of using a reduced complexity model for marine cloud brightening with frontal cyclone and stratus cumulus clouds, and emphasizes the need to also consider background droplets size and concentration than just meteorological conditions.

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Knockdown of the glucosamine-6-phosphate N-acetyltransferase gene by RNA interference enhances the virulence of entomopathogenic fungi against rice leaffolder Cnaphalocrocis medinalis - Muhammad Shakeel; Ashraf Khan; Juan Du; Abdul Basit; Guangming Yang; Khalid Haddi; Sohail Abbas; Aleena Alam; Shangwei Li (Pesticide Biochemistry and Physiology, 2024)

Microbial Ecosystems as Guardians of Food Security and Water Resources in the Era of Climate Change - Muhammad Danish Toor; Muneeb Ur Rehman; Javeria Abid; Dibyajyoti Nath; Izhar Ullah; Abdul Basit; Muhammad Mughees Ud Din; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

High-temperature stress in strawberry: understanding physiological, biochemical and molecular responses - Izhar Ullah; Muhammad Danish Toor; Bayram Ali Yerlikaya; Heba. I. Mohamed; Seher Yerlikaya; Abdul Basit; Attiq ur Rehman (Planta, 2024)

Identification of bacterial community in a rapid composting method using 16SrDNA genes sequencing - Muhammad Shahid; Waqar Ahmed; Abdul Basit Khan; Zafar Iqbal Shams; Afsheen Arif (Biodegradation, 2024)

Erratum to: Endophytic Fungi as Potential Bio-Control Agents of Soil-Borne Pathogen - Murad Muhammad; Abdul Basit; Kashif Ali; Wen-Jun Li; Li Li; Heba I. Mohamed (Journal of Crop Health, 2024)

Endophytic Fungi as Potential Bio-Control Agents of Soil-Borne Pathogen - Murad Muhammad; Abdul Basit; Kashif Ali; Wen-Jun Li; Li Li; Heba I. Mohamed (Journal of Crop Health, 2024)

Study loss of vegetative cover and increased land surface temperature through remote sensing strategies under the inter-annual climate variability in Jinhua–Quzhou basin, China - Shahzad Ali; Abdul Basit; Sajid Ali; Muhammad Umair; Tyan Alice Makanda; Mohammed Rafi Shaik; Mujeeb Khan (Environmental Science and Pollution Research, 2024)

Enhancing the Quality and Fruit Yield of Sweet Cherry (Prunus Avium) Cultivars by Foliar Application of Boron - Muhammad Sajid; Abdul Basit; Syed Tanveer Shah; Ayesha Khan; Izhar Ullah; Muhammad Bilal; Muhammad Suleman Khan; Waleed Khan (Applied Fruit Science, 2024)

Impacts of climate and land coverage changes on potential evapotranspiration and its sensitivity on drought phenomena over South Asia - Shahzad Ali; Abdul Basit; Muhammad Umair; Jian Ni (International Journal of Climatology, 2024)
Understanding the spatiotemporal historical drought pattern and their sensitivity effect on potential evapotranspiration (PET) and vegetation coverage changes is essential for efficient drought mitigation policies under climate change. In this study, we used the standardized precipitation evapotranspiration index (SPEI) at multiple timescales, such as SPEI‐01, SPEI‐03, SPEI‐06, SPEI‐09 and SPEI‐12; we explored their regional‐scale dry and wet annual changes across seven sub‐regions of South Asia from 1902 to 2018. Results suggest that from 1981 to 2018, the extreme drought of SPEI has increased in South Asia, which mostly affects the summer and winter growing seasons, that is, SPEI‐06 to SPEI‐12 across seven sub‐regions of South Asia. The frequency of drought events during dry and wet annual changes of SPEI had an extremely dry year starting from 1998 to 2018, which mostly affected the South Asia region. Data from the past 18 years showed that the land changing detection has increased in the forests, cultivated land, arid land, savanna and farmland; by contrast, there has been significantly reduced permanent ice and snow, mixed forests, open shrub, grasslands, permanent wetlands, water bodies and evergreen broadleaf forests. Seasonal SPEI presented diverse characteristics such as showing a dry trend in Afghanistan, India, Pakistan and Sri Lanka during autumn and winter. Afghanistan and Bhutan are wet during the summer compared with other sub‐regions of South Asia, with drought frequency occurring at 45.3% and 44.4%. Sri Lanka, Pakistan and India are the driest regions in South Asia due to their high drought frequency, duration and intensity. The correlation between PET and crop water stress index (CWSI), PET and regional ET p reduction (Er) indicated a considerably negative correlation, while a significantly positive correlation was found between CWSI and Er, NDVI and Er. This study provides a comprehensive assessment of climate and vegetation coverage changes on PET, ET and SPEI, and can help in formulating long‐term adaptive strategies to reduce the cumulative impacts of droughts.

Ultraviolet-B radiation in relation to agriculture in the context of climate change: a review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Hira Nawaz; Izhar Ullah; Abdul Basit; Heba I. Mohamed (Cereal Research Communications, 2024)

A review on endophytic fungi: a potent reservoir of bioactive metabolites with special emphasis on blight disease management - Murad Muhammad; Abdul Basit; Kashif Ali; Haris Ahmad; Wen-jun Li; Ayesha Khan; Heba I. Mohamed (Archives of Microbiology, 2024)

Potential Role of Vermicompost in Abiotic Stress Tolerance of Crop Plants: a Review - Muhammad Danish Toor; Rıdvan Kizilkaya; Izhar Ullah; Lyubka Koleva; Abdul Basit; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2023)

Nanotechnology: an Integrated Approach Towards Agriculture Production and Environmental Stress Tolerance in Plants - Izhar Ullah; Muhammad Danish Toor; Abdul Basit; Heba I. Mohamed; Mohammed Gamal; Nouraiz Ahmed Tanveer; Syed Tanveer Shah (Water, Air, & Soil Pollution, 2023)

Chemical profiling and biological activities of Dipterygium glaucum Decne.: An in-vivo, in-vitro and in-silico evaluation - Afia Shahid; Duraiz Ahmed Khan; Hanan Y. Aati; Asmaa E. Sherif; Chitchamai Ovatlarnporn; Musaddique Hussain; Huma Rao; Muhammad Imran Khan; Muhammad Younus; Abdul Basit; Kashif ur Rehman Khan (South African Journal of Botany, 2023)

Load Frequency Control of Marine Microgrid System Integrated with Renewable Energy Sources - Guoqiang Zhang; Irfan Ahmed Khan; Amil Daraz; Abdul Basit; Muhammad Irshad Khan (Journal of Marine Science and Engineering, 2023)
In seaports, low-carbon energy systems and energy efficiency have become increasingly important as a result of the evolution of environmental and climate change challenges. In order to ensure the continued success of seaports, technological advancements must be introduced to a number of systems, such as seaport vehicles, harbor cranes, and the power sources of berthed ships. Harbor areas might need a microgrid to handle these aspects. Typically, microgrids that substitute conventional generator units with renewable energy sources (RES) suffer from system inertia problems, which adversely affect microgrid frequency stability. A load frequency controller (LFC) based on a novel modified proportional integral derivative with filter (MPIDF) is presented in this paper for enhancing the performance of marine microgrid system (MMS). The serval optimization algorithm (SOA), a recent bio-inspired optimization algorithm, is used to optimize the MPIDF controller coefficients. This controller is tested on a marine microgrid containing a number of RES such as wind turbine generators, sea wave energy, and solar generation. The efficacy of the proposed MPIDF controller is verified with respect to other controllers such as PIDF and PI. Similarly, the proposed meta-heuristic algorithm is validated as compared to other algorithms including particle swarm optimization (PSO), ant colony optimization (ACO), and jellyfish swarm optimization (JSO). This study also evaluates the robustness of the proposed controller to different perturbations in step load, changes in system parameters, and other parameter variations.

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Efficacy of cow and buffalo dung on vermiremediation and phytoremediation of heavy metals via Fourier-transform infrared spectroscopy and comet assay - Anum Naseer; Saiqa Andleeb; Abdul Basit; Shaukat Ali; Muhammad Siraj ud-Din; Nazish Mazhar Ali; Iram Liaqat; Aisha Nazir (Environmental Science and Pollution Research, 2022)

Application of RNAi technology: a novel approach to navigate abiotic stresses - Izhar Ullah; Ehab A. R. Kamel; Syed Tanveer Shah; Abdul Basit; Heba I. Mohamed; Muhammad Sajid (Molecular Biology Reports, 2022)

Types, sources, socioeconomic impacts, and control strategies of environmental noise: a review - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Allah Ditta; Predrag Ilic; Muhammad Amin; Abdul Basit Naveed; Aadil Gulzar (Environmental Science and Pollution Research, 2022)

Impact assessment of drought monitoring events and vegetation dynamics based on multi-satellite remote sensing data over Pakistan - Shahzad Ali; Abdul Basit; Jian Ni; Manzoor; Fahim Ullah Khan; Muhammad Sajid; Muhammad Umair; Tyan Alice Makanda (Environmental Science and Pollution Research, 2022)

Molecular Evidence and Hematological Profile of Bovines Naturally Infected with Ehrlichiosis in Southern Punjab, Pakistan - Muhammad Abdul Basit; Muhammad Ijaz; Jawaria Ali Khan; Kamran Ashraf; Rao Zahid Abbas (Acta Parasitologica, 2022)

Microwave-Assisted Physically Cross-Linked Chitosan-Sodium Alginate Hydrogel Membrane Doped with Curcumin as a Novel Wound Healing Platform - Hassan A. Albarqi; Abdulsalam A. Alqahtani; Irfan Ullah; Nauman Rahim Khan; Hafiz Muhammad Basit; Tayyaba Iftikhar; Abdul Wahab; Muhammad Ali; Muhammad Badar (AAPS PharmSciTech, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Arif Malik; Muhammad Abdul Basit Ashraf; Muhammad Waqas Khan; Ayesha Zahid; Hassan Shafique; Sulayman Waquar; Siew Hua Gan; Muhammad Ashraf (Archives of Environmental Contamination and Toxicology, 2020)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)